2011
DOI: 10.1021/ja2014746
|View full text |Cite
|
Sign up to set email alerts
|

Isolablep- andm-[(tBu2MeSi)2Si]2C6H4: Disilaquinodimethane vs Triplet Bis(silyl radical)

Abstract: Isomeric p- and m-disilaquinodimethanes 2 and 4 were synthesized by the reductive dehalogenation of the corresponding p- and m-bis(halosilyl)benzenes 1 and 3, respectively, and were isolated and structurally characterized. The X-ray diffraction and solid-state NMR studies of 2 revealed its singlet quinodimethane structure featuring two exocyclic Si═C double bonds with some singlet biradical contribution. In contrast, the X-ray crystallography and EPR measurements of 4 disclosed its biradical nature, described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 32 publications
1
42
0
5
Order By: Relevance
“…It contains a four-coordinate silicon atom ( Figure 1). In contrast to the known triplet biradical, [7] compound 2 has only one silicon atom, the coordination of which is completely different. The silicon dichloride unit is coordinated by two cyclic alkyl(amino)carbene (L 1 D) ligands to adopt a distorted tetrahedral geometry around the Si atom.…”
Section: CLmentioning
confidence: 91%
See 3 more Smart Citations
“…It contains a four-coordinate silicon atom ( Figure 1). In contrast to the known triplet biradical, [7] compound 2 has only one silicon atom, the coordination of which is completely different. The silicon dichloride unit is coordinated by two cyclic alkyl(amino)carbene (L 1 D) ligands to adopt a distorted tetrahedral geometry around the Si atom.…”
Section: CLmentioning
confidence: 91%
“…In contrast, stable triplet biradicals of main group elements are rare. Recently Sekiguchi et al [7] reported a triplet diradical with two silicon atoms prepared by reduction of a meta-substituted bissilyl phenyl derivative with KC 8 . Power [8] and Lee et al reviewed persistent stable free radicals of Group 14.…”
Section: Dedicated To Professor Heribert Offermanns On the Occasion Omentioning
confidence: 99%
See 2 more Smart Citations
“…4,5,13,27 On the other hand, in 2011, the synthesis of the Sidisubstituted para-and meta-quinodimethane derivatives was reported. 28 It is experimentally found that the para-derivative exhibits singlet ground state together with the smaller bondlength alternation (BLA) of the central benzene ring (0.053 Å) as compared to that of the all-carbon analogue, Thiele's hydrocarbon (0.103 Å). 29 This experimental observation evokes the presence of larger contribution of the open-shell resonance structure in the para-quinodimethane framework for this synthesized system.…”
Section: Introductionmentioning
confidence: 99%